Metformin targets brown adipose tissue in vivo and reduces oxygen consumption in vitro. Issue 9 (8th June 2018) - Breining, Peter; Jensen, Jonas B.; Sundelin, Elias I.; Gormsen, Lars C.; Jakobsen, Steen; Busk, Morten; Rolighed, Lars; Bross, Peter; Fernandez‐Guerra, Paula; Markussen, Lasse K.; Rasmussen, Nanna E.; Hansen, Jacob B.; et al.
Abstract : Aims: To test the hypothesis that brown adipose tissue (BAT) is a metformin target tissue by investigating in vivo uptake of [ 11 C]‐metformin tracer in mice and studying in vitro effects of metformin on cultured human brown adipocytes. Materials and methods: Tissue‐specific uptake of metformin was assessed in mice by PET/CT imaging after injection of [ 11 C]‐metformin. Human brown adipose tissue was obtained from elective neck surgery and metformin transporter expression levels in human and murine BAT were determined by qPCR. Oxygen consumption in metformin‐treated human brown adipocyte cell models was assessed by Seahorse XF technology. Results: Injected [ 11 C]‐metformin showed avid uptake in the murine interscapular BAT depot. Metformin exposure in BAT was similar to hepatic exposure. Non‐specific inhibition of the organic cation transporter (OCT) protein by cimetidine administration eliminated BAT exposure to metformin, demonstrating OCT‐mediated uptake. Gene expression profiles of OCTs in BAT revealed ample OCT3 expression in both human and mouse BAT. Incubation of a human brown adipocyte cell models with metformin reduced cellular oxygen consumption in a dose‐dependent manner. Conclusion: These results support BAT as a putative metformin target.